PELATIHAN MICROSOFT OFFICE WORD UNTUK MENINGKATKAN KEGIATAN PEMBELAJARAN PADA SMP NEGERI 02 MARGOYOSO - Galuh Saputri; Ria Ester; Agung Siswopranoto (Abdi Jurnal Publikasi, 2023)
The participation of technology and information is currently very much needed, especially in the current era of the Industrial Revolution 4.0. Junior high school (SMP) students are required to have more skills than to face the challenges of technological developments in general. Because in the junior high school curriculum an independent learning curriculum has been implemented, which means implementing face-to-face learning programs and project system learning. SMP Negeri 02 Margoyoso is one of the junior high schools that implements the independent learning curriculum program. At this school there are no subjects that specifically conduct further discussions regarding the use of Microsoft Office applications on Windows such as Excel, Word and Power Point. Although this application is very useful for students, especially with vocational offices. This application is useful both in doing schoolwork or activities in the environment around them. For this reason, this Microsoft Office training was held so that it can improve student learning both in carrying out daily tasks at school and as their basic provision after leaving school later, so that it can be applied in high school or when they are in college and work environment. The aim of this community partnership program is to improve students' computer skills, especially Microsoft Word, Excel and Power Point. At least as easy as Microsoft Word, Excel and Power Point, with the specific tools they use to create financial reports such as using margins, entering text into tables, formatting dates and times, and using formulas for addition, subtraction, division and multiplication and drafting forms precise and correct mathematical logic that can be applied to complete tasks and obligations at SMP Negeri 02 Margoyoso.